Fungicidal Management of Alternaria Blight in Rapeseed (Brassica rapa L.) - Subedi, Subash; Sah, Santosh Kumar; Neupane, Saraswati; Shrestha, Jiban (Agronomy Journal of Nepal, 2025)
Alternaria blight caused by Alternaria spp. is a major bio-bottleneck to rapeseed production in Nepal. Field experiments were conducted during the winter seasons of 2023 and 2024 at the Oilseed Research Program (ORP), Nawalpur, Sarlahi to evaluate the comparative efficacy of fungicides against Alternaria blight and their influence on yield of rapeseed. The trials were laid out in a randomized complete block design with seven treatments ancozeb 75% WP @ 2.5 g/L, Azoxystrobin 23% EC (Amistar) @ 1 g/L, Tebuconazole 25% EC (Folicur) @ 1 g/Ll, Fenamidone 50% SC (Reason) @ 1 g/L, Trifloxystrobin 50% WG (Flint) @ 0.5 g/L, Chlorothalonil 50% SC (Bravo) @ 3 g/L including control (Water spray) and three replications using the variety Nawalpur Tori 4. All allocated fungicidal treatments were applied as two foliar sprays at 60 and 75 days after sowing following the onset of disease. Fungicide application significantly (P